The XPO1 Inhibitor KPT-8602 Ameliorates Parkinson’s Disease by Inhibiting the NF-κB/NLRP3 Pathway - Liu, Shuhan; Wang, Shengxiang; Gu, Runze; Che, Na; Wang, Jing; Cheng, Jinbo; Yuan, Zengqiang; Cheng, Yong; Liao, Yajin (Frontiers in Pharmacology, 2022)
XPO1 (exportin1) is an important transport receptor that mediates the nuclear export of various proteins and RNA. KPT-8602 is a second-generation XPO1 inhibitor with the least side effects, which has been used for cancer treatment in clinical trial. Previous studies indicate parts of the first-generation XPO1 inhibitors hold anti-inflammation activities, which may increase its indication in future. Here, we show that KPT-8602 exerts potent anti-inflammatory effect both in vitro and in vivo. Mechanistically, KPT-8602 inhibits the activation of the NF-κB pathway and the NLRP3 inflammasome by blocking the phosphorylation and degradation of IκBα. Importantly, administration of KPT-8602 could attenuate both lipopolysaccharide-induced perioral inflammation and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine induced neuroinflammation in vivo. In addition, the tissue damages were also ameliorated by KPT-8602, indicating that KPT-8602 could be used as a novel potential therapeutic agent for treating the NF-κB and NLRP3 inflammasome-driven diseases, such as Parkinson’s disease.